From a canción perdida to a Third Millennium Cassandra, or Maria Rosa Lojo building an identity - Grillo, Rosa Maria (Anales de Literatura Hispanoamericana, 2021)
Galicia and New World always seem destined to constitute an unalterable binomial, from that Finisterrae soIberian and at the same time already located beyond the Columns of Hercules and outside the Mare Nostrum. Through the autobiographical narrative and the essays by the Argentine writer María Rosa Lojo, a few moments, characters and topoi of the migration/exile of Galicians to Argentina are analyzed.
Keywords: María Rosa Lojo; Argentina; Galicia; migration literature